The backhand - Which one (or two) to use? - Reid, M. (coachesinfo.com)
The backhand in tennis is characterised for segment interaction, racket velocity, segment interaction, reach, skill acquisition, disguise and for the he open stance backhand. Conclusion: Although recent research (and the modern game for that matter) points to the two handed backhand holding certain advantages over the one-handed technique, coaches should continue to work with their players to find the most suitable backhand stroke for each individual. With each player's physical characteristics, coordinative ability and playing style vastly different, rather than develop a personalised backhand preference, similar to those that plagued the coaching of the past, coaches should be encouraged to assist the player develop his or her "own" backhand stroke.